Revisiting the minimum wage-employment debate: Throwing out the baby with the bathwater? - David Neumark; J. M. Ian Salas; William Wascher (Institute for the Study of Labor (IZA), 2013)
We revisit the minimum wage-employment debate, which is as old as the Department of Labor. In particular, we assess new studies claiming that the standard panel data approach used in much of the new minimum wage research is flawed because it fails to account for spatial heterogeneity. These new studies use research designs intended to control for this heterogeneity and conclude that minimum wages in the United States have not reduced employment. We explore the ability of these research designs to isolate reliable identifying information and test the untested assumptions in this new research about the construction of better control groups. Our evidence points to serious problems with these research designs. We conclude that the evidence still shows that minimum wages pose a tradeoff of higher wages for some against job losses for others, and that policymakers need to bear this tradeoff in mind when making decisions about increasing the minimum wage.
Keywords: J23; J38; 330; minimum wage; employment; control groups